Hydrofluoric acid adsorption diaphragm for lithium iron phosphate battery, preparation method of hydrofluoric acid adsorption diaphragm and battery

By coating the separator of lithium iron phosphate batteries with a metal-organic framework adsorption layer, the problem of hydrofluoric acid corrosion was solved, the battery life and safety were improved, and efficient hydrofluoric acid capture and battery stability were achieved.

CN121076401APending Publication Date: 2025-12-05天能新能源(湖州)有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511432298.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-09
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing lithium iron phosphate batteries suffer from shortened lifespan and reduced safety due to hydrofluoric acid corrosion during cycling. Current modification schemes also present problems such as reduced ion transport channels, increased risk of internal short circuits, and aggravated side reactions.

Method used

Metal-organic framework materials containing zirconium or aluminum oxygen clusters and nitrogen-containing organic ligands are used as hydrofluoric acid adsorption coatings. These coatings are applied to a substrate layer and capture hydrofluoric acid through efficient physical and chemical adsorption. Combined with conductive additives and binders, a stable coating is formed with a pore size distribution between 0.5 and 1.0 nm, which enhances the selective adsorption of HF.

Benefits of technology

It achieves efficient capture of hydrofluoric acid, improves battery life, stability and safety, reduces interface impedance and gas production, and extends battery cycle life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a hydrofluoric acid adsorption diaphragm for a lithium iron phosphate battery, a preparation method of the hydrofluoric acid adsorption diaphragm and the battery and belongs to the technical field of adsorption functional diaphragms of lithium iron phosphate batteries. The hydrofluoric acid adsorption diaphragm comprises a base material layer and a hydrofluoric acid adsorption coating coated on the base material layer, the hydrofluoric acid adsorption coating internally comprises a metal organic framework material prepared from oxygen clusters of metal zirconium or aluminum and nitrogen-containing organic ligands, and the pore size distribution of more than 90% of pores in the metal organic framework material is between 0.5 nm and 1.2 nm; and the hydrofluoric acid adsorption coating further comprises a conductive additive and a binder. The hydrofluoric acid adsorption coating has excellent hydrofluoric acid adsorption capacity, so that the use stability and safety of the lithium iron phosphate battery can be effectively improved, and the service life of the lithium iron phosphate battery can be effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of adsorption functional separators of lithium iron phosphate batteries, and particularly relates to a separator for in-situ capturing of HF gas generated in the cycle process of a lithium iron phosphate battery, a preparation method of the separator, and a battery with a long service life. BACKGROUND

[0002] As a mainstream system of power batteries, the cycle life and safety of lithium iron phosphate (LiFePO4) batteries are severely restricted by the corrosion problem of hydrogen fluoride (HF). The root cause of the problem lies in the chemical instability of lithium salt LiPF6 in the electrolyte, that is, under the battery operating environment, LiPF6 first pyrolyzes to generate highly active PF5, and then PF5 reacts with trace water (even if controlled at <20 ppm) in the system to continuously generate HF gas.

[0003] On the positive side of the battery, HF corrodes the LiFePO4 crystal structure, causing Fe 3+ ions to dissolve, directly causing loss of active material. Experimental studies have shown that for every 100 ppm of HF accumulated in the electrolyte, the positive electrode capacity attenuation rate increases by 3-5%. On the negative side of the battery, HF attacks the lithium carbonate component in the SEI film, forcing the SEI film to repeatedly break and reform, causing the film thickness to increase and the interface impedance to rise (impedance increases by more than 50% after 100 cycles). In addition, HF has a pitting effect on the aluminum current collector, causing the battery internal resistance to increase rapidly (contact resistance increases by up to 200%), and accelerating the gas generation side reaction. When the concentration of HF exceeds 200 ppm, the battery gas production expands to three times, significantly increasing the risk of thermal runaway.

[0004] To address the corrosion problem of HF, two main separator modification schemes have been developed in the industry:

[0005] (1) By coating nano ceramic particles (particle size 100-500 nm) on the surface of polyolefin separators (PE / PP), the thermal stability of the ceramic material is used to improve the heat resistance of the separator (closed pore temperature >200℃), and an attempt is made to capture the corrosive gas through the acid-base reaction of metal oxides with HF;

[0006] In this scheme, Al2O3 reacts irreversibly with HF, and the generated AlF3 is insoluble solid, gradually blocking the membrane micropores, leading to a decrease in ion transport channels. Experiments show that after 50 cycles, the porosity of the membrane decreases by 40%, and the ionic conductivity decreases from 0.8 mS / cm to 0.5 mS / cm; at the same time, the water molecules generated in the reaction further react with PF5 (PF5+H2O→POF3+2 HFPFX5+HX2OPOFX3+2HF), forming a HF regeneration cycle, so that the concentration of HF in the system rebounds only in the short term; further, the crystallization of AlF3 leads to the embrittlement of the coating, and the coating peels off during the charging and discharging process, aggravating the risk of internal short circuit of the battery.

[0007] (2) Using polymers containing polar groups (such as -OH, -NH2) (such as polydopamine PDA, chitosan) to form a physical barrier layer, which adsorbs HF through intermolecular forces;

[0008] In this scheme, the specific surface area of the polymer is low (<100 m 2 / g), and the chemical adsorption capacity of its amino group to HF is only 0.05~0.1 mmol / g (about 2~4 mg / g), which is much lower than the amount of HF accumulated in the battery cycle (typical value: 1 Ah battery generates 20~30 mg HF); at the same time, the dense polymer layer significantly increases the Li + diffusion resistance (coating surface resistance >10 Ω·cm 2 ), causing charging and discharging polarization, and the rate performance decreases by >30%; further, the nitrogen-containing polymer is oxidized and decomposed at high voltage (>4.0 V vs. Li + / Li), releasing NH3 and other gases (gas production >0.5 mL / Ah), which will accelerate the swelling of the battery. SUMMARY

[0009] The present application further improves the separator of lithium iron phosphate battery in order to solve the above technical problems. One of the purposes of the present application is to provide a preparation method of a hydrofluoric acid adsorption separator for a lithium iron phosphate battery, the second purpose is to provide a corresponding adsorption separator, and the third purpose is to provide a corresponding battery.

[0010] The specific technical solutions are described below:

[0011] The hydrofluoric acid adsorption separator for the lithium iron phosphate battery comprises a substrate layer and a hydrofluoric acid adsorption coating layer coated on the substrate layer;

[0012] The hydrofluoric acid adsorption coating layer comprises a metal-organic framework material made of metal zirconium or aluminum oxide clusters and nitrogen-containing organic ligands, and more than 90% of the pore size distribution of the metal-organic framework material is between 0.5~1.2 nm;

[0013] The hydrogen fluoride adsorption coating also comprises a conductive additive and a binder.

[0014] In a preferred embodiment, the nitrogen-containing organic ligand is selected from 2-amino terephthalic acid, 2,5-diamino terephthalic acid or 3-amino-1,2,4-triazole.

[0015] In a further preferred embodiment, the metal-organic framework material is UiO-66-NH2or MIL-101-NH2(Al).

[0016] As a metal-organic framework material, UiO-66-NH2is formed by linking oxygen clusters of zirconium ions and amino-containing terephthalic acid (NH2-BDC), and MIL-101-NH2(Al) is formed by linking oxygen clusters of aluminum ions and 2-amino terephthalic acid (NH2-BDC).

[0017] In a preferred embodiment, the loading amount of the metal-organic framework material in the hydrogen fluoride adsorption coating is 0.2-1.0 mg / cm 2 , and the thickness of the hydrogen fluoride adsorption coating is 1-5 μm.

[0018] In a preferred embodiment, the molar ratio of the oxygen cluster of metal zirconium or aluminum in the metal-organic framework material to the nitrogen-containing ligand is 1:(1-1.5).

[0019] The preparation method of the hydrogen fluoride adsorption separator for lithium iron phosphate batteries comprises the following steps:

[0020] S1: dispersing metal-organic framework material nanoparticles, a conductive additive and a binder in a solvent according to a mass ratio of (80-95):(5-15):(3-8) to obtain a slurry, wherein the metal-organic framework material nanoparticles are made of oxygen clusters of metal zirconium or aluminum and nitrogen-containing organic ligands;

[0021] S2: coating the slurry onto the surface of the substrate layer to form a wet coating layer;

[0022] S3: drying the substrate layer coated with the wet coating layer to obtain a separator.

[0023] In a preferred embodiment, the particle size of the metal-organic framework material nanoparticles is between 100-300 nm.

[0024] In a preferred embodiment, the nitrogen-containing organic ligand is selected from 2-amino terephthalic acid, 2,5-diamino terephthalic acid or 3-amino-1,2,4-triazole.

[0025] In a further preferred embodiment, the metal organic framework material is UiO-66-NH2, MIL-101-NH2(Al).

[0026] A lithium ion battery comprising a positive electrode, a negative electrode, an electrolyte and an adsorption separator, wherein the adsorption separator is the adsorption separator prepared by any of the technical solutions described above.

[0027] The positive electrode comprises a lithium iron phosphate material.

[0028] In summary, the technical solution of the present application has the following main beneficial effects:

[0029] Compared with the prior art, the adsorption separator provided by the technical solution of the present application has at least three core advantages:

[0030] The metal organic framework material in the hydrofluoric acid adsorption coating has a high specific surface area (2000-6000 m 2 / g), which is 3-5 times that of activated carbon, and can provide a large number of physical adsorption sites; at the same time, the metal nodes (such as Zr 4+ , Al 3+ ) can form a coordination bond with F - , which has a binding energy of more than 150 kJ / mol, realizing efficient chemical adsorption of HF.

[0031] Further, the pore size range of the metal organic framework material is controlled to be between 0.5-1.2 nm, which is highly matched with the dynamic diameter of HF molecules (0.44 nm), thereby improving the selective adsorption performance.

[0032] Further, by introducing nitrogen-containing groups such as amino groups (-NH2) into the organic ligand, the acid-base interaction force of the metal organic framework material in the hydrofluoric acid adsorption coating can be enhanced, thereby further improving the adsorption capacity.

[0033] At the same time, the crystal structure retention rate of the organic framework material in the embodiment is more than 95% after being soaked in commercial electrolyte (1M LiPF6 / EC+DMC) for 30 days, indicating that it has practical application feasibility, wherein M is molar concentration, EC is ethylene carbonate, and DMC is dimethyl carbonate.

[0034] That is, the battery has advantages in stability, safety and service life.

[0035] Further or more detailed beneficial effects will be described in the specific embodiments in combination with specific examples. DETAILED DESCRIPTION

[0036] The present application will be further explained in combination with the embodiments:

[0037] The core technical problem of the technical scheme of the embodiments of the present application is derived from the accurate understanding of the prior art by the inventor, therefore, how to avoid the loss of the service life of the lithium iron phosphate battery caused by the hydrofluoric acid as much as possible is a technical problem that the inventor needs to solve urgently.

[0038] It should be noted that the embodiments do not constitute a limitation on the protection scope of the claims of the present application, and the technical solutions that can be reasonably expected by the skilled in the art according to the technical concepts provided / proved by the embodiments should be covered within the protection scope of the claims of the present application.

[0039] The embodiments are described in detail as follows:

[0040] Firstly, regarding the synthesis of the organic framework material (MOFs) material:

[0041] Embodiment 1:

[0042] The preparation of UiO-66-NH2 is as follows:

[0043] 1. ZrCl4 particles with an average particle size of about 200 nm (2.33 g) and 2-amino terephthalic acid (1.81 g) are dissolved in DMF (100 mL);

[0044] 2. Acetic acid (3 mL) is added as a regulator, and the solvothermal reaction is carried out at 120℃ for 24 h;

[0045] 3. The reaction solution is centrifuged and washed, and the white powder, UiO-66-NH2, is obtained after methanol elution for 48 h and vacuum activation.

[0046] Embodiment 2:

[0047] The preparation of MIL-101-NH2(Al) is as follows:

[0048] 1. Aluminum nitrate nonahydrate (Al(NO3)3·9H2O) (0.75 g, 2.0 mmol) and 2-amino terephthalic acid (NH2-BDC) (0.36 g, 2.0 mmol) are dissolved in a mixed solvent composed of 15 mL N,N-dimethylformamide (DMF) and 1 mL deionized water in a high-pressure reaction kettle;

[0049] 2. The reaction kettle is sealed and placed in a blast oven at 130℃ for 12 hours;

[0050] 3. After natural cooling to room temperature, a light yellow precipitate is obtained by centrifugation (8000 rpm, 10 min). The precipitate is washed with DMF and anhydrous ethanol for 3 times respectively to remove the unreacted ligand and metal salt;

[0051] 4. Vacuum dried for 12 hours to obtain the activated MIL-101-NH2(Al) material as a light yellow powder.

[0052] Comparative Example 1:

[0053] The difference from Example 1 is that Mg is used as the metal adsorption site of MOFs, and the steps are as follows:

[0054] 1. Dissolve magnesium nitrate hexahydrate (Mg(N03)2-6H20) (1.28 g, 5.0 mmol) and 2,5-diaminoterephthalic acid (NH2-H4DOBDC) (0.55 g, 2.5 mmol) in a mixed solvent (DMF : ethanol : water = 15 : 2 : 2, v / v / v) and ultrasonic treatment until completely dissolved;

[0055] 2. Transfer the solution to a high-pressure reaction kettle and react at 125°C for 20 hours;

[0056] 3. After natural cooling, obtain a yellow precipitate by centrifugation. Wash with DMF for 3 times to remove unreacted substances, and then elute with ethanol for 24 hours to replace the solvent molecules in the pores;

[0057] 4. Vacuum activation at 150°C for 12 hours to obtain the activated Mg-MOF-74-NH2 material as a yellow powder.

[0058] Comparative Example 2:

[0059] The difference from Example 1 is that ZrCl4 particles with hydroxyl groups to reduce the average particle size of the pore size are used to prepare MOFs, and the steps are as follows:

[0060] 1. Dissolve ZrCl4 (2.33 g) and 2,5-dihydroxyterephthalic acid (DHBDC) (1.99 g) in DMF (100 mL). Add 8 mL of glacial acetic acid as a modulator. React at 120°C for 24 hours. The subsequent washing and activation steps are the same as Example 1;

[0061] 2. Expected pore size: 0.6 nm.

[0062] Comparative Example 3:

[0063] The difference from Example 1 is that terephthalic acid (H2BDC) organic ligand is used to prepare MOFs, and the steps are as follows:

[0064] 1. Except that the ligand is replaced by equimolar amount (1.66 g) of H2BDC, the remaining steps (amount of metal salt, solvent, modulator, reaction temperature and time, post-treatment process) are completely consistent with Example 1 (UiO-66-NH2).

[0065] 2. The rest of the steps (metal salt amount, solvent, modulator, reaction temperature and time, work-up process) are exactly the same as Example 1 (UiO-66-NH2) except that the ligand is replaced by equimolar amount (1.66 g) of H2BDC.

[0066] The following Table 1 shows the performance parameters of the MOFs prepared in Examples 1-2 and Comparative Examples 1-3:

[0067] Table 1 Performance parameters of the MOFs prepared in Examples 1-2 and Comparative Examples 1-3 Pore size distribution (nm) of 90% of the pores Specific surface area (m 2 / g)]]> HF adsorption capacity (mmol / g) Crystal structure retention rate (%) after immersion in commercial electrolyte (1M LiPF6 / EC+DMC) for 30 days Example 1 0.75-0.85 1250 1.8 >95 Example 2 1..0~1.6 2100 1.5 >95 Comparative Example 1 1.2 1800 1.5~1.8 >95 Comparative Example 2 0.6-0.8 1050 0.9 >95 Comparative Example 3 0.8 1200 0.75 >95

[0068] The test method for pore size distribution and specific surface area in Table 1 is that the specific surface area of the material is measured by nitrogen adsorption-desorption test (BET method), and a physical adsorption analyzer is used to test the adsorption-desorption isotherm of N2 of the material at 77 K. The specific surface area is calculated by BET model, and the pore size distribution is calculated by NLDFT or BJH model.

[0069] The test method for HF adsorption capacity is that a gas adsorption device is used to test the static adsorption capacity of the material for HF gas. A vapor adsorption analyzer is used to expose the sample to HF vapor at 0.5 atm in a constant temperature environment of 25°C, and the mass change of the sample is monitored in real time by a high-precision microbalance to calculate the adsorption amount.

[0070] The test method for crystal structure retention rate is X-ray diffraction analysis (XRD). The cycled battery is disassembled in an inert atmosphere glove box, the separator coating sample is taken out, washed with DMC solvent and sealed in a special sample holder. An X-ray diffractometer is used for testing. By comparing the changes of intensity, position and half-width of the characteristic diffraction peaks before and after cycling, the crystal structure stability is qualitatively or quantitatively evaluated.

[0071] As can be seen from Table 1, the MOFs prepared in Examples 1-2 all have a pore size distribution matching the molecular kinetic diameter of HF, and have a high specific surface area and HF adsorption capacity, and the crystal structure retention rate can reach more than 95% after soaking in commercial electrolyte (1M LiPF6 / EC+DMC) for 30 days;

[0072] Comparative Example 1 has a significant decrease in HF adsorption capacity compared with Example 1 because Mg is used instead of Zr as the metal adsorption site; the pore size distribution of Comparative Example 2 is quite different from the molecular kinetic diameter of HF and does not match, resulting in a decrease in HF adsorption capacity compared with Example 1; Comparative Example 3 does not use N-containing organic ligand, and the force acting on HF is lower than that of Example 1, which shows that the HF adsorption capacity is lower than that of Example 1.

[0073] The preparation method of the corresponding hydrofluoric acid adsorption separator membrane of Example 1 is as follows:

[0074] Slurry formulation (mass ratio):

[0075] UiO-66-NH2nanopowder (200 nm): 90%, single-walled carbon nanotubes (SWCNT, length > 5 μm): 5%, PVDF (HSV900): 5% were dispersed in NMP solvent, and the dispersion was carried out by ball milling process, ball-to-material ratio 5:1, rotation speed 350 rpm, time 3 hours, to obtain a slurry with solid content 15 wt%.

[0076] Coating process:

[0077] The substrate was a 16 μm PE separator membrane, and the coating method was microgravure coating. The slurry was coated on one side of the substrate, the coating speed was 2 m / min, and the coating tension was controlled at 10 N / m, to obtain a wet coating layer with a thickness of 10 μm.

[0078] Drying and curing:

[0079] Drying in a vacuum oven at 80°C for 12 h to obtain the separator membrane.

[0080] The preparation method of the corresponding adsorption separator membrane of Example 2 and Comparative Examples 1-3 is the same as that of Example 1.

[0081] Table 2 below shows the performance parameters of the separator membranes prepared in Examples 1-2 and Comparative Examples 1-3:

[0082] Table 2 Performance parameters of the separator membranes prepared in Examples 1-2 and Comparative Examples 1-3 MOFs loading (mg / cm 2 ])]] Dry film thickness (pm) Porosity (%) Example 1 0.85 3.2 55 Example 2 0.5 2.8 60 Comparative Example 1 0.88 3.1 57 Comparative Example 2 0.82 3.0 48 Comparative Example 3 0.88 3.1 53

[0083] The test method of MOFs loading in Table 2 is the weight difference method;

[0084] The mass of the clean and dry base film (M1) was measured using a precision balance (accuracy 0.01 mg).

[0085] The total mass of the functional separator membrane after coating and thorough drying (M2) was measured.

[0086] MOFs loading = (M2 - M1) / coating area.

[0087] The test method of dry film thickness is step gauge measurement.

[0088] The test method of porosity is n-butanol adsorption method.

[0089] The following Table 3 is the service life parameters of the lithium batteries corresponding to the separators prepared in Examples 1-2 and Comparative Examples 1-3, which use lithium iron phosphate (LiFeP04) material as the positive electrode, graphite as the negative electrode, and a carbonate organic solvent containing 1M LiPF6 as the electrolyte:

[0090] Table 3 Performance parameters of the batteries corresponding to the separators prepared in Examples 1-2 and Comparative Examples 1-3 Battery life (80% EOL) Interfacial impedance (Rct, %) Gas production (mL / Ah) Example 1 ~1500 65% 0.8 Example 2 ~1400 70% 1.0 Comparative Example 1 ~500 200% 4.5 Comparative Example 2 ~1000 95% 1.8 Comparative Example 3 ~800 120% 2.5

[0091] The battery service life test standards in Table 3 refer to GB / T 31486-2015 "Power Storage Battery for Electric Vehicles: Electrical Performance Requirements and Test Methods".

[0092] As can be seen from Table 3, the batteries corresponding to Examples 1 and 2 exhibit overall and significant advantages in cycle life, interface stability, gas production inhibition, material structure integrity, and thermal safety. The batteries corresponding to Comparative Examples 1-3 have more side reactions due to the decline in the adsorption performance of HF, and there is a great risk in the later stage of the service life.

[0093] In the description of the present specification, the description of the terms "embodiment", "basic embodiment", "preferred embodiment", "other embodiment", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0094] Although the preferred embodiments of the present application have been described, those skilled in the art can make additional changes and modifications to the embodiments once they know the basic inventive concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications falling within the scope of the present application.

[0095] Obviously, those skilled in the art can make various modifications and variations to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.

Claims

1. A hydrofluoric acid adsorbing separator membrane for lithium iron phosphate batteries, characterized in that, The adsorption separator comprises a substrate layer and a hydrofluoric acid adsorption coating layer coated on the substrate layer. The metal organic framework material is made of oxygen clusters of zirconium or aluminum and nitrogen-containing organic ligands, and the pore size distribution of more than 90% of the pores in the metal organic framework material is between 0.5 and 1.2 nm. The hydrofluoric acid adsorption coating layer further comprises a conductive additive and a binder.

2. The adsorptive septum of claim 1, wherein: The nitrogen-containing organic ligand is selected from 2-amino terephthalic acid, 2,5-diamino terephthalic acid, or 3-amino-1,2,4-triazole.

3. The adsorptive septum of claim 2, wherein: The metal organic framework material is UiO-66-NH2, MIL-101-NH2(Al), or MIL-96(Al).

4. The adsorptive septum of claim 1 or 3, wherein: The metal organic framework material is loaded in the hydrofluoric acid adsorption coating at a loading amount of 0.2-1.0 mg / cm 2 The thickness of the hydrofluoric acid adsorption coating is 1-5 μm.

5. The adsorptive septum of claim 2, wherein: The molar ratio of the oxygen clusters of zirconium or aluminum to the nitrogen-containing ligand in the metal organic framework material is 1: (1-1.5).

6. A process for the preparation of hydrofluoric acid adsorbing separator membrane for lithium iron phosphate battery characterized by, The method comprises the following steps: S1: dispersing nanoparticles of a metal organic framework material, a conductive additive, and a binder in a solvent at a mass ratio of (80-95):(5-15):(3-8) to obtain a slurry, wherein the nanoparticles of the metal organic framework material are made of oxygen clusters of zirconium or aluminum and nitrogen-containing organic ligands; S2: coating the slurry onto the surface of the substrate layer to form a wet coating layer; S3: drying the substrate layer coated with the wet coating layer to obtain a separator.

7. The method of claim 8, wherein: The particle size of the nanoparticles of the metal organic framework material is between 100 and 300 nm.

8. The method of claim 8, wherein: The nitrogen-containing organic ligand is selected from 2-amino terephthalic acid, 2,5-diamino terephthalic acid, or 3-amino-1,2,4-triazole.

9. The method of claim 9, wherein: The metal organic framework material is UiO-66-NH2, MIL-101-NH2(Al), or MIL-96(Al).

10. A lithium-ion battery comprising a positive electrode, a negative electrode, an electrolyte and a sorptive separator, characterized in that: The adsorption separator is the adsorption separator of any one of claims 1-5, or is prepared by the method of any one of claims 6-9. The positive electrode comprises a lithium iron phosphate material.

Citation Information

Patent Citations

  • Mesoporous alumina ceramic coated diaphragm and preparation method thereof

    CN111969161A

  • Nanometer porous composite diaphragm, preparation method thereof and lithium ion battery

    CN119852644A